2013
DOI: 10.3168/jds.2012-6170
|View full text |Cite
|
Sign up to set email alerts
|

Volatiles and sensory evaluation of goat milk cheese Gokceada as affected by goat breeds (Gokceada and Turkish Saanen) and starter culture systems during ripening

Abstract: The effect of goat breed and starter culture on volatile composition and sensory scores in goat milk cheese was studied during 90d of ripening. Milk from 2 goat breeds (Gokceada and Turkish Saanen) and different starter culture systems (no starter, mesophilic and thermophilic starters) were used in the manufacture of goat milk cheeses (called Gokceada goat cheese). Volatile composition was determined by a solid-phase microextraction-gas chromatography-mass spectrometric method. Sixty compounds including esters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 34 publications
0
56
0
Order By: Relevance
“…As reported by Hayaloglu et al [38] , the most important esters in the goat's cheese were ethyl hexanoate, ethyl octanoate and ethyl decanoate in Turkish cheeses of the goat's milk Gokceada and Saanen. Ethyl acetate formed from lactose by lactic bacteria (LAB); citrate and lactate metabolism, or as a product of the catabolism of amino acids is an important flavor compound in many cheeses.…”
Section: Estersmentioning
confidence: 77%
See 3 more Smart Citations
“…As reported by Hayaloglu et al [38] , the most important esters in the goat's cheese were ethyl hexanoate, ethyl octanoate and ethyl decanoate in Turkish cheeses of the goat's milk Gokceada and Saanen. Ethyl acetate formed from lactose by lactic bacteria (LAB); citrate and lactate metabolism, or as a product of the catabolism of amino acids is an important flavor compound in many cheeses.…”
Section: Estersmentioning
confidence: 77%
“…Methyl groups such as 3-Methyl-hexane and 2-Methylhexane are present at d 50 with higher levels than at 72 d, unlike toluene, which was more concentrated at 72 d. Relative to toluene; Hayaloglu et al [38] reported that they have obtained similar results with the Gokceada goat's milk cheese at 90 d. The levels of compounds found in farmhouse production were close to those reported by Medjoudj et al [7] for Bouhezza goat cheese at 72 d. It is possible that these similarities are due to the region where these cheeses were produced (wilaya of Tebessa), thus the same vegetation, climate and environmental conditions for the goats producing the raw matter.…”
Section: Miscellaneous Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…They also act as precursors of other aromatic compounds, like methyl ketones, alcohols, aldehydes, lactones and esters (Collins et al, 2003). During cheese ripening, carboxyl acids can occur in three primary biochemical ways: lipolysis, proteolysis and lactose fermentation (McSweeney and Sousa, 2000;Delgado et al, 2010;Hayaloglu et al, 2013c). According to the results of research of the aromatic profile of 11 Turkish cheeses, Hayaloglu and Karabulut (2013a) mention butyric acid, acetic acid and caproic acid as the most present, both in Tulum cheese that ripens in an animal skin and in other Turkish cheeses, which is in accordance with the research results of Vrdoljak (2016) on ewe cheese in a sack.…”
Section: Carboxyl Acidsmentioning
confidence: 99%